2018
DOI: 10.1038/s41467-018-07523-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical loading of desmosomes depends on the magnitude and orientation of external stress

Abstract: Desmosomes are intercellular adhesion complexes that connect the intermediate filament cytoskeletons of neighboring cells, and are essential for the mechanical integrity of mammalian tissues. Mutations in desmosomal proteins cause severe human pathologies including epithelial blistering and heart muscle dysfunction. However, direct evidence for their load-bearing nature is lacking. Here we develop Förster resonance energy transfer (FRET)-based tension sensors to measure the forces experienced by desmoplakin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 56 publications
10
71
0
Order By: Relevance
“…Moreover, fluorophores with fast maturation rates, high extinction coefficients, and sufficient photostability are advantageous. Tension sensor studies using FRET pairs with yellow/red (Austen et al., ; Price et al., ; Ringer et al., ), green/red (Kumar et al., ; LaCroix, Lynch, Berginski, & Hoffman, ), or blue/yellow (Borghi et al., ; Price et al., ) emission spectra have been published. For the special case of tension sensor multiplexing (i.e., the simultaneous measurement of two tension sensors) the two orthogonal pairs mTFP1/ShadowG and LSSmOrange/mKate2 are available (Demeautis et al., ; Ringer et al., ).…”
Section: Strategic Planningmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, fluorophores with fast maturation rates, high extinction coefficients, and sufficient photostability are advantageous. Tension sensor studies using FRET pairs with yellow/red (Austen et al., ; Price et al., ; Ringer et al., ), green/red (Kumar et al., ; LaCroix, Lynch, Berginski, & Hoffman, ), or blue/yellow (Borghi et al., ; Price et al., ) emission spectra have been published. For the special case of tension sensor multiplexing (i.e., the simultaneous measurement of two tension sensors) the two orthogonal pairs mTFP1/ShadowG and LSSmOrange/mKate2 are available (Demeautis et al., ; Ringer et al., ).…”
Section: Strategic Planningmentioning
confidence: 99%
“…Other applied donor‐only controls are constructs in which only the donor fluorophore is inserted into the POI. This control is easier to generate but does not mimic as precisely the microenvironment that the donor fluorophore is exposed to in the tension sensor construct (Price et al., ).…”
Section: Strategic Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] In line with this, it was demonstrated that desmosomes experience tension when keratinocytes are exposed to mechanical strain. 4 Autoantibodies present in patients with PV (PV-IgG) are known to primarily target desmoglein (Dsg)1 and Dsg3, the cadherin-type adhesion molecules in desmosomes. 5 The mucosal-dominant subtype of PV (mdPV) is believed to be caused primarily by anti-Dsg3 antibodies, whereas the mucocutaneous type (mcPV) is caused by autoantibodies targeting both Dsg1 and 3.…”
Section: What Is the Translational Message?mentioning
confidence: 99%
“…Pemphigus vulgaris (PV) represents an autoimmune disease characterized by suprabasal blister formation due to loss of keratinocyte cohesion in stratified epithelia such as skin and oral mucosa that are subjected to substantial shear forces . In line with this, it was demonstrated that desmosomes experience tension when keratinocytes are exposed to mechanical strain . Autoantibodies present in patients with PV (PV‐IgG) are known to primarily target desmoglein (Dsg)1 and Dsg3, the cadherin‐type adhesion molecules in desmosomes .…”
mentioning
confidence: 93%